Antenas de microfita anulares cilíndricas embutidas - Tiago Braga Ventura (2009)
This work presents an analysis of cavity-backed cylindrical wraparound antennas. The cavity is filled by a dielectric, called substrate, and is built within an infinite cylindrical conductor. The effects of the cavity on the radiation pattern and input impedance are presented. The analysis is based on equivalence principle and method of moments. The equivalence principle allows the problem to be split into 2 regions, inside and outside the cavity, connected by an equivalent surface magnetic current distribution. The magnetic current is expanded in a set of basis functions, with coefficients that are determined from integral equations that follow from the boundary conditions. The knowledge of the currentdistribution allows the calculation of radiation fields, and the input impedance, from the fields inside the cavity. Results are presented and compared to those for a cylindrical microstrip antenna, and to those from using cavity method, also presented.